Slx5/Slx8 Promotes Replication Stress Tolerance by Facilitating Mitotic Progression - Yee Mon Thu (Cell Reports, 2016)
Loss of minichromosome maintenance protein 10 (Mcm10) causes replication stress. We uncovered that S. cerevisiae mcm10-1 mutants rely on the E3 SUMO ligase Mms21 and the SUMO-targeted ubiquitin ligase complex Slx5/8 for survival. Using quantitative mass spectrometry, we identified changes in the SUMO proteome of mcm10-1 mutants and revealed candidates regulated by Slx5/8. Such candidates included subunits of the chromosome passenger complex (CPC), Bir1 and Sli15, known to facilitate spindle assembly checkpoint (SAC) activation. We show here that Slx5 counteracts SAC activation in mcm10-1 mutants under conditions of moderate replication stress. This coincides with the proteasomal degradation of sumoylated Bir1. Importantly, Slx5-dependent mitotic relief was triggered not only by Mcm10 deficiency but also by treatment with low doses of the alkylating drug methyl methanesulfonate. Based on these findings, we propose a model in which Slx5/8 allows for passage through mitosis when replication stress is tolerable.